2021
DOI: 10.1371/journal.pone.0247807
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided fine needle aspiration cytology and ultrasound examination of thyroid nodules in the UAE: A comparison

Abstract: Background Thyroid nodules are a common clinical finding and most are benign, however, 5–15% can be malignant. There is limited regional data describing the accuracy of ultrasound-guided fine needle aspiration (FNA) cytological examination compared to ultrasound examination of thyroid in patients who have undergone thyroid surgery. Methods A retrospective analysis of ultrasonographic (US) reports, FNA cytology reports and histopathology reports of 161 thyroid nodules presented at the endocrine center at Tawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thyroid USG was very accurate when combined with FNAB by Salam et al, although, unlike the current study, that study did not employ any reference standards (morphological properties of the nodule) to limit the chances of FN results. 4 The positive and negative probability ratios were 6.90 (95% CI: [2. the combined effect of sensitivity and specificity, with an inclination of the curve towards the upper left, showing high quality of thyroid US diagnostic accuracy. Azizi et al investigated the hypothesis stating that three-dimensional ultrasound (3-D-US) allows for distinguishing benign from malignant thyroid nodules with better sensitivity and specificity than two-dimensional ultrasound (2-D-US).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid USG was very accurate when combined with FNAB by Salam et al, although, unlike the current study, that study did not employ any reference standards (morphological properties of the nodule) to limit the chances of FN results. 4 The positive and negative probability ratios were 6.90 (95% CI: [2. the combined effect of sensitivity and specificity, with an inclination of the curve towards the upper left, showing high quality of thyroid US diagnostic accuracy. Azizi et al investigated the hypothesis stating that three-dimensional ultrasound (3-D-US) allows for distinguishing benign from malignant thyroid nodules with better sensitivity and specificity than two-dimensional ultrasound (2-D-US).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, different TIRADS guidelines [4][5][6][7][8] are available, including American College of Radiology (ACR) -TIRADS, American Thyroid Association (ATA) -TIRADS, American Association of Clinical Endocrinology/American Clinical Endocrinology/American Medical Endocrinology (AACE/ACE/AME) -TIRADS, Korean Society of Thyroid Radiology (KSR)/(KSThR) -TIRADS, and European Thyroid Association (ETA)/(EU) -TIRADS. These TIRADS provide a list of notable morphological features reported in the US images as a gold standard to classify a suspected nodule as malignant or benign.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ratios stabilizing after 2012, probably due to the UAE adopting more sensitive thyroid cancer diagnostic testing including genetic testing. 17,18 The differences between Emirati and expats ratio may be due to a mixture of the population pyramid of expats arriving to the UAE for economic purposes and possibly medical tourism. 19 In addition, the analysis showed that another risk factor for thyroid cancer in the UAE is age, where the highest frequency (17.5%) of thyroid cancer patients tends to be between 35-39 years of age and around 47.8% of the patients tend to be between 30-44 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially valuable in cases of undetermined biopsy results. Al-Salam et al estimated that UG-FNAB and ultrasonography are key tools in predicting malignancy in TNs [ 30 ]. The authors suggest that because TNs with Bethesda III and IV diagnoses may present a higher risk of malignancy, greater US vigilance is required [ 30 ].…”
Section: Discussionmentioning
confidence: 99%